Wave Energy Linear Motor/Generator - Mohd, Muhammad Hadfiz (Universiti Teknologi Petronas, 2008)
This project reports on how to generate electricity from ocean wave by using permanent magnet linear generator. The objectives of this project are to design and build a small scale linear generator powered by ocean wave energy that able to generate at least 1 kW of electricity. It is not easy to harness wave energy and convert it into electricity in large amounts. So, the studies for this project include finding information and knowledge related to the topic besides developing skill through enquiry and literature review. Linear electric generators are linear motion electromagnetic devices that transform short stroke oscillatory motion mechanical energy into electrical energy. The linear generator in this project consists of a stator and a translator as its major part. In linear generator, electrical power is generated simply by forced relative movement of linear generator to its stator. The linear generator will oscillates with the wave up and down to cut electromagnetic flux inside the stator. Thus, the cuts of magnetic flux will result as electricity. To become a successful project, several things need to be reviewed like literature review on linear generator, design and development of the generator, experiment of prototype before gaining result and correct data. By varying the frequency of the wave energy, the cuts of magnetic flux depends on the cycle movement and the speed of the translator into the stator. Then, the line voltage and line current was measured to calculate the total output power that has been generating by linear generator. The results show that the output voltage and hence not unexpectedly, the output power, depends to a large extent on the translator speeds. As a result, the wave energy linear generator ouly generates a small amount of output power that not achieves the objective of this project.